Solid tissue culture for cytogenetic analysis: a collaborative survey for the Association of Clinical Cytogeneticists. Issue 8 (August 1996) - Rodgers, C S; Creasy, M R; Fitchett, M; Maliszewska, C T; Pratt, N R; Waters, J J
Abstract : AIMS: To survey the diagnostic service provided by UK laboratories for the culture of solid tissue samples (excluding tumours) and in particular to examine the variation in culture success rates and the problems of maternal cell overgrowth. METHODS: Twenty seven laboratories took part in a collaborative survey during 1992. Each laboratory submitted data on up to a maximum of 60 consecutive specimens (n = 1361) over a six month period. RESULTS: Skin specimens, the largest category received (n = 520), were the most problematic (51% success rate). Culture success rates were significantly lower (43%) when skin specimens (n = 140) were transported dry to the laboratory. Success rates for skin specimens also varied, depending on the origin of the specimen, from 18% for intra-uterine deaths (IUD) (n = 94) to 85% for neonatal deaths (n = 33) and 83% for live patients (n = 54). Culture of selected extra-fetal tissues from IUD, stillbirths and following elective termination of pregnancy (TOP) gave comparable success rates to those achieved for skin samples from neonatal deaths and live births. Skewed sex ratios, female > male, were identified for products of conception (POC) (n = 298) and placental biopsy specimens (n = 97). CONCLUSIONS: By appropriate selection, transport and processing of tissues, and in particular by avoiding relying solely on skin samples from IUD, stillbirths and TOP, an increase in culture success rates for solid tissue samples submitted for cytogenetic analysis could be achieved. The high risk of maternal cell contamination from POC and placental biopsy specimens was also identified in this survey.